The Wiley Blackwell companion to tourism - Lew, Alan A.; Hall, C. Michael; Williamns, Allan M. (West Sussex, United Kingdom Wiley Blackwell, 2014)
The Wiley Blackwell Companion to Tourism presents a collection of readings that represent an essential and authoritative reference on the state-of-the-art of the interdisciplinary field of tourism studies. It presents a comprehensive and critical overview of tourism studies across the social sciences and introduces emerging topics and reassesses key themes in tourism studies in the light of recent developmentsIncludes 50 newly commissioned essays by leading experts in the social sciences from around the world, It also contains cutting-edge perspectives on topics that include tourism's role in globalization.
Includes bibliographical references and index.
Keywords: Tourism -- Handbooks, manuals, etc